An ex-ante analysis of the effects of the UK government's welfare reforms on labour supply in Wales - Stuart Adam; David Phillips (Institute for Fiscal Studies (IFS), 2013)
The UK is part-way through almost unprecedented real-terms reductions in government expenditure as the government attempts to deal with the large hole in the public finances. As part of this, the UK government has announced and is in the process of implementing 18 billion of cuts to welfare spending (that is, spending on benefits and tax credits) by 2014. It has also announced plans to begin the national roll-out of a new Universal Credit from October 2013, which will replace six means-tested benefits with a single integrated benefit. Universal Credit represents the most significant change in the structure of the welfare system since the 1940s and is aimed at reducing administration costs and errors, simplifying claims, encouraging take-up and strengthening the incentive to work for those currently facing the weakest work incentives...
Keywords: 330